Implementasi Media Pembelajaran “Box Up Materi Negara Anggota ASEAN” dalam Penerapan Pembelajaran Berdiferensiasi - Firmansyah Miftafurohim; Tri Asih; Heri Maria Zulfiati (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Differentiated learning is an educational approach that caters to and acknowledges the varying abilities, interests, and learning styles of pupils. Media education Box Up is an educational medium presented in the format of an Explosion Box. The objective of this best practice is to investigate the functionality of “Box Up” Learning Media in the implementation of Differentiated Learning at SDN Pleret Lor, assess the potential of “Box Up” Learning Media in the implementation of Differentiated Learning at SDN Pleret Lor, and evaluate the effectiveness of “Box Up” Learning Media in the implementation of Differentiated Learning at SDN Pleret Lor. The study design employed is qualitative descriptive in order to examine the implementation of the Differentiated learning paradigm. The findings indicated that Grade 6 students at SDN Pleret Lor achieved an average score of 46 after engaging in learning activities prior to utilising the "Box Up" Learning Media. Learning after utilising Box Up Learning Media yielded superior outcomes compared to learning before to its use, with an average score of 75. Consequently, there was a 29% improvement in learning outcomes. This phenomenon occurs due to the utilisation of "Box Up" Learning Media, which has been proven to enhance the passion of sixth-grade pupils at SD Negeri Pleret Lor.